Investigation of pollen release by poricidal anthers using mathematical billiards - Hansen, Matheus; Lanes, Gabriel C.; Brito, Vinícius L. G.; Leonel, Edson D. [UNESP] (American Physical Society (APS), 2021)
Buzz pollination is described using a mathematical model considering a billiard approach. Applications to a rough morphology of a typical poricidal anther of a tomato flower (Solanum lycopersicum) experiencing vibrations applied by a bumblebee (Bombus terrestris) are made. The anther is described by a rectangular billiard with a pore on its tip while the borders are perturbed by specific oscillations according to the vibrational properties of the bumblebee. Pollen grains are considered as noninteracting particles that can escape through the pore. Our results not only recover some observed data but also provide a possible answer to an open problem involving buzz pollination.
Keywords: Non-interacting particles; Observed data; Pollen grains; Solanum lycopersicum; Vibrational properties